REAP, a project for PET and can - Velosa, Ana (Journal of Sustainability Perspectives, 2022)
In a moment of change, with an impulse from the pandemic that hit the world, the pursuit of the Sustainable Development Goals has become a clear necessity towards a more sustainable world, with less inequalities and a basis for the upbringing of future generations. SDG Goal 12 Sustainable Consumption and Production, 13 - Climate Action - and 14 - Life below water - are clearly linked to plastic and metal consumption and production. Also, Goal 10 - Reduced inequalities - plays its paper in this field. Not only does plastic and metal production, consumption and use need to be reformed, but also producers need to bridge inequalities and reuse, recycle and introduce circular economies in their own countries, not inducing mass imposition of waste in poorer economies. With this in mind, at the University of Aveiro, the REAP Project (Recycling of PET and Aluminium Packages) is being implemented, together with a Norwegian partner, with vast experience in the plastic waste sector. This project will help create the idea of PET and aluminium impact from a tax on these packages inside campi walls and a tax return after adequate deposition. Tracking these numbers and promoting research in the area of PET and aluminium reuse are a further input towards the implementation of SDGs.The paper will explain the project, its goals and ambitions.Keyword: PET, Can, SDG Goals, circular economy